Cover Image, Volume 51, Issue 1. Issue 1 (28th November 2018) - Wait, Elizabeth E.; Masunov, Artëm E.; Vasu, Subith S.
Abstract : On the cover : The cover image is based on the Article Quantum Chemical and Master Equation Study of OH + CH2 O → H2 O + CHO Reaction Rates in Supercritical CO2 Environment by Elizabeth E. Wait et al., https://doi.org/10.1002/kin.21228